The EFFECT OF MICROORGANISM NUTRITION ON THE FERMENTATION PROCESS ON BIOETHANOL CONCENTRATION FROM TOBACCO STALKS - Bekti Palupi; Boy Arief Fachri; Istiqomah Rahmawati; Meta Fitri Rizkiana; Helda Wika Amini; Nikita Meidi; Dini Rahmawaty (UNEJ e-Proceeding, 2022)
Tobacco is one of the abundant biomass resources, especially in Jember Regency. Tobacco stalk has potential as a raw material for bioethanol and has more economic value than just being used as firewood. One of the new renewable energy that comes from biomass is biofuel. The currently developed biofuels are biodiesel and bioethanol. Compared to fuel oil, bioethanol's advantages include having a high octane number (106-110), increasing combustion efficiency, and reducing pollutant emissions. Besides being used to fulfill energy needs, bioethanol can also be used as a raw material in the pharmaceutical, cosmetic, and various alcohol derivatives industries. The Covid-19 pandemic has also made the need for ethanol increase. The scarcity of hand sanitizer products has made the price soar. The raw material for the hand sanitizer is ethanol, so the need for ethanol also increases. Bioethanol production, in general, has a 4-step process. The processes are pretreatment, hydrolysis, fermentation, and distillation. This study focused on the fermentation process with the aim of knowing the effect of microorganism nutrition on the concentration of bioethanol from tobacco stalks. Fermentation is done with the yeast Saccharomyces Cerevisiae. The addition of nutrients in the fermentation process greatly affects the concentration of ethanol that will be produced. The addition of optimal nutrients in this study was shown in the addition of 1.3% of the total initial volume of the sample or 0.325gram with a concentration result of 23.9%. Keywords: bioethanol, microorganism nutrition, fermentation, tobacco stalks